Buddův-Chiariho syndrom a TIPS--12 let zkuseností - Safka, V; Hůlek, P; Krajina, A; Dulícek, P; Fejfar, T; Jirkovský, V; Pozler, O; Vańásek, T (Casopis lekaru ceskych, 2005)
BACKGROUND: Massive thrombosis of hepatic veins is clinically the most serious type of Budd-Chiari syndrome (BCS). Ischemic impairment is the basic problem in case of acute or fulminate course of BCS. Restitution of blood drainage within the liver is a key therapeutic approach in such situation. In chronic course of the disease, symptoms of portal hypertension as ascites, G1 bleeding or hepatorenal syndrome are more common. The portosystemic shunt leads both to blood outflow restitution and to the decrease of portal hypertension. TIPS is a promising method due to minimal perioperative risk for the patient in critical situation and also due to its easiness of use. The aim of our study was to determine the clinical outcome in patients with BCS treated by TIPS in a retrospective analysis. METHODS AND RESULTS: During 12 years 23 patients with intraparenchymal thrombotic occlusion of hepatic veins were treated using TIPS, 17% were children, only 4 patients (17%) were men, the median age was 33.3 years (range 13 to 75 years). One third of the procedures was performed as urgent. In 2/3 of patients thrombosis developed in relation to myeloproliferative syndrome, in nearly 1/3 the origin of thrombosis was not detected. In 2 patients a defect of coagulation was revealed. In the first 11 patients the bare stent was used, the consecutive 12 patients received the ePTFE covered stent (stentgraft). Six patients died during follow-up: I due to fulminate liver failure, 2 due to liver failure caused by acute shunt occlusion, 1 due to the progression of the underlying hematooncological disease; the reason of death in 2 patients was not known. One patient was treated by OLTx during follow-up. The 17 surviving patients are in good condition with good shunt function although they need anticoagulant therapy and intermittent reinterventions. The average period between revisions was 2-3 years, 2 patients had no revision of TIPS for 4 years. The use of ePTFE covered stents had no effect on the number of early occlusions (approx. 18%), the occurrence of late stenoses and occlusions was substantially decreased (p=0.04, log-rank test). CONCLUSIONS: Standing on this experience we consider TIPS, in accordance with literature data, an advantageous therapeutic approach in Budd-Chiari syndrome caused by massive liver vein thrombosis. If the follow up treatment is rigorous, the TIPS usually ensures the necessary perfusion and the function of the liver So it may spare the patients of objectionable liver transplantation.
Keywords: transjugulární intrahepatální portosystémový zkrat; dospělí; Humans; Budd-Chiari Syndrome; lidé středního věku; Middle Aged; Portasystemic Shunt, Transjugular Intrahepatic; stenty; mužské pohlaví; Adult; Adolescent; Stents; Buddův-Chiariho syndrom; ženské pohlaví; lidé; mladiství; Aged; senioři; Male; Female